Wildlife on the wind: a field biologist's journey and an Indian reservation's renewal - Smith, Bruce L., author; Utah State University Press, publisher (Colorado State University. Libraries, 2010)
In the heart of Wyoming sprawls the ancient homeland of the Eastern Shoshone Indians, who were forced by the U.S. government to share a reservation in the Wind River basin and flanking mountain ranges with their historical enemy, the Northern Arapahos. Both tribes lost their sovereign, wide-ranging ways of life and economic dependence on decimated buffalo. Tribal members subsisted on increasingly depleted numbers of other big game—deer, elk, moose, pronghorn, and bighorn sheep. In 1978, the tribal councils petitioned the U.S. Fish and Wildlife Service to help them recover their wildlife.
Gettin' there -- On the reservation -- First elk -- Mountains and sky -- Stranded -- The way it was -- Younger kids -- On the same page -- Game code -- Upshot.
Keywords: Shoshoni Indians -- Ethnobiology -- Wyoming -- Wind River Indian Reservation; Arapaho Indians -- Ethnobiology -- Wyoming -- Wind River Indian Reservation; Wildlife management -- Wyoming -- Wind River Indian Reservation; Biology -- Fieldwork -- Wyoming -- Wind River Indian Reservation; Wind River Indian Reservation (Wyo.); Smith, Bruce L., 1948-